Low-cost toilet-based sit-to-stand device for elderly with lower limb weakness - Yootho, Thanakorn; Pititheeraphab, Yutthana (Bulletin of Applied Sciences, 2026)
Falls in the bathroom pose a serious risk to older adults, leading to physical and psychological consequences and a reduced quality of life, including fractures, head injuries, fear of movement, and loss of independence. These falls result from both personal factors, such as muscle weakness, impaired balance, chronic conditions, and medication side effects, and environmental factors, including slippery floors, inadequate lighting, insufficient assistive devices, and unsuitable sanitary fixtures. This research aimed to design and develop a low-cost toilet-based sit to stand device for elderly with lower limb weakness that can be used with both standard and multipurpose toilet bowls. The device supports safe and comfortable transitions between sitting and standing and is designed based on biomechanical principles of the sit-to-stand movement. The system comprises a mechanical unit with a linear electric actuator, an electrical control system, a C-based control program, and a battery-powered energy source. Biomedical engineering tests confirmed correct operation and stable performance of the control and safety systems. Biomedical tests confirmed stable control and safety performance. The device safely supported loads of 10–120 kg. Lifting time ranged from 11.73–16.15 s, while lowering time ranged from 11.14–12.93 s. In 30 volunteers (15 males, 15 females), knee flexion angles decreased after device use from 86.07–89.93° to 60.70–72.90° in males and from 78.10–88.13° to 59.10–67.90° in females, indicating reduced knee joint load during sit-to-stand. These results indicate that the device effectively reduces biomechanical load on the knee joint during the sit-to-stand movement.